Family Communication at the End of Life. Issue 3 (2nd July 2016) - Keeley, Maureen P.
ABSTRACT: This article presents a brief review examining what research has been conducted exploring family communication at the end of life (EOL) and suggestions for future research at the end-of-life context. Future research areas include: 1) the role of culture, 2) family member role and relational climate, 3) ethical considerations in regard to methodological choices, 4) the role of emotional and cognitive development on EOL communication, 5) EOL backstage communication, 6) death circumstances, and 7) the use of interdisciplinary research teams.